2021
DOI: 10.3390/antiox10111720
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Photoprotection Efficiency of Sunscreens Containing Antioxidants under Disinfection Conditions

Abstract: Sunscreens ensure thorough protection against sunburn. The delivery of UV filters into the stratum corneum and viable epidermis could be reduced by the use of antioxidants (such as β-carotene and trans-resveratrol, alone or combined). The presence/absence of antioxidants (trans-resveratrol and β-carotene) in formulations containing benzophenone-3 (UV-filter) and their efficiency under disinfection and neutral conditions are studied and compared. The trial was conducted on 38 people. The prepared ointments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This means that it can act as both an oxidizing agent, generating reactive oxygen species (ROS), and as an antioxidant, scavenging free radicals and reducing oxidative stress. 6 In line with this Janus-faced behaviour, GA was previously described to enhance or inhibit tumour development.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This means that it can act as both an oxidizing agent, generating reactive oxygen species (ROS), and as an antioxidant, scavenging free radicals and reducing oxidative stress. 6 In line with this Janus-faced behaviour, GA was previously described to enhance or inhibit tumour development.…”
Section: Introductionmentioning
confidence: 80%
“…11 In this case, GA's ability to counteract oxidative stress by scavenging free radicals underpins its activity as inhibitor in cancer progression. 6,8,12 Particularly for osteosarcoma cells, Ching-Lung and coworkers found that GA treatment of U2-OS cells suppressed cell migration due to the down-regulation of PKC, mitogen-activated protein kinase (MAPK), and PI3K/AKT, resulting in inhibition of MMP-2 and MMP-9 expressions. 12 In view of the multifaced activity, development of GAconjugated materials is a vastly studied field.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, 46 a controlled clinical trial was conducted on 38 volunteers (age: 20-60; female: 28; male: 10) to whom an area of the forearm was irradiated with an UV-B light. To conduct the study, the consent of Slovenian National Medical Ethics Committee was obtained (16 May 2018, No.…”
Section: Experiments Of Chlorination Of Benzophenone and Resveratrol ...mentioning
confidence: 99%
“…Various botanicals endowed with antioxidant activity are emerging as new natural photoprotective compounds, including Curcuma longa extract and trans-resveratrol, the latter being a highly used antioxidant in sunscreens [ 31 , 32 , 33 ]. In this context, the natural extract from Polypodium leucotomos (Fernblock ® , FB) has been shown to exert antioxidant and photoprotective effects against UVA light in keratinocytes and fibroblasts, the two main cellular components of the skin [ 33 , 34 , 35 , 36 , 37 ]. Additionally, it leads to decreased oxidative damage by enhancing antioxidant cellular mechanisms in skin cells upon exposure to fine pollutant particles (PM 2.5 ) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%